Herbal Bonding Agent-Going Natural - Sanshavi Ponnamma, A. R.; Shoaib Ulla Khan, A.; Baby, Belwin; B. Reddy, Goutham; Somaiah, Sanju; Muddaiah, Sunil; Shetty, B. K. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Introduction: There are various types of bonding agents and generations have evolved over time. Bonding agents play a pivotal role in the field of orthodontics. Through this article we would like to highlight the effects of natural herbal products on the shear bond strength and their effect on enamel surface. Objectives: To determine the effect of natural herbal products on enamel surface after etching, de-bonding and clean up through scanning electron microscope. To compare the efficacy of a naturally occurring antioxidant Amla(Indian Gooseberry),Lemon And Aloe Vera in adjunction with carboxymethylcellulose(CMC) in normalizing the shear bond strength of enamel. Background: In this in-vitro study we will evaluate the effect of Amla(Phyllantus Embilica ,Indian Gooseberry),Lemon And Aloe Vera extract in adjunction with carboxymethylcellulose (CMC) on the shear bond strength of composite resin to etched enamel. Method: Forty extracted premolars were divided into 4 equal groups consisting of 10 each: Group 1 - Control group. Group 2 - Amla extract adjunct as bonding agent. Group 3 - Aloe vera extract adjunct as bonding agent. Group 4 - Lemon extract adjunct as bonding agent. Shear Bond strength was checked using Universal Testing Machine Results: Results showed that Amla as a bonding agent has the highest shear bond strength followed by Lemon, Conventional bonding agent and Aloevera. Shear bond strength of Amla was significantly higher than that of conventional bonding agent.